Design of a temperature-limited emission current controller - Jarosław Sikora; Dariusz Kuś (AIP Advances, 2023)
In this study, we design and test a current controller for a source of thermionic electron emission operating in an ionization vacuum gauge. We use a precise and controlled source of current to transfer the emission current from the anode, which has a high potential in the circuit, to the cathode with a low potential. This eliminates the need for galvanic isolation or sources of floating voltage, which introduce noise to the system, for supplying the cathode and the anode. We show that this has a limited effect in terms of changes in the residual gas pressure on the emission current in the range from 10−4 to 10−2 Pa. The temporal stability of the emission current was determined for reference values ranging from 1 to 4 mA for both 10-min and 2-h periods, and it was found to be lower than 6 ppm. The proposed controller can be used in apparatus to measure electron impact-induced gas ionization.